The Influence Of Project Based Learning (Pjbl) For Students Creative Thinking Ability Of Twelfth Grade At Yabhinka Welding Techniques Vocational High School In Cilegon - Helleni Febnesia; Atep Iman; Deddy Supriyatna (Yayasan Adra Karima Hubbi, 2023)
The purpose of this study is to examine the impact of the Project Based Learning (PjBL) learning model on the creative thinking skills of Twelfth Class Welding Engineering students at Yabhinka Vocational High School in Cilegon. This research employs a quantitative approach and a quasi-experimental methodology. Students of Twelfth Class Welding Engineering at Yabhinka Vocational High School for the academic year 2020/2021 comprised the research sample, with of Twelfth Class Welding Engineering 1 comprising 18 student samples serving as the experimental class and class of Twelfth Class Welding Engineering 2 totaling 18 student samples serving as the control class. The data collection instrument was an essay-based, 10-question test of creative reasoning abilities. Examine the hypothesis using the Paired Sample t Test and Independent Test in this study. The posttest mean is 82.9, the mean observation value is 86.11, and the project mean is 84.14, according to the results of the study conducted in of Twelfth Class Welding Engineering 1, which employs the Project Based Learning (PjBL) learning model. of Twelfth Class Welding Engineering 2 students who did not use the Project Based Learning (PjBL) learning model achieved a posttest mean of 71.7, an observation mean of 74.56, and a project mean of 49.9. The results of hypothesis testing with the Independent t-test statistic show a significant value of 0.000 or less than 0.05, so it can be concluded that the Project Based Learning (PjBL) learning model has an effect on the creative thinking abilities of of Twelfth Class Welding Engineering.